Dogs don't wear sneakers - Numeroff, Laura Joffe; Mathieu, Joseph (New York : Simon & Schuster Books for Young Readers, 1993)
In a child's imagination, animals do wacky things, including ducks riding bikes, yaks skiing, and fish eating bagels.
NP
Keywords: Animals -- Fiction; Imagination -- Fiction; Stories in rhyme